Citrate pathophysiology and metabolism. Issue 1 (February 2017) - Monchi, Mehran
Abstract: By chelating ionized calcium, citrate allows extracorporeal circuit anticoagulation without a bleeding risk for the patient. Citrate anticoagulation is also associated with a reduced activation of leucocytes and platelets. Citrate clearance by citric acid cycle (Krebs cycle) is not modified by renal failure, but is reduced by about 50% in patients with cirrhosis. Toxic effects of citrate result from a decrease in plasma ionized calcium of the patient. The first side effect is a prolongation of the QT interval. Clinical signs of hypocalcemia and hypotension in humans appear below 0.9 mmol/L of plasma ionized calcium.